PENGARUH PERBEDAAN KONSTRUKSI MATA PANCING DAN JENIS UMPAN TERHADAP HASIL TANGKAPAN KAKAP MERAH (Lutjanus argentimaculatus) DENGAN PANCING ULUR (hand line) DI PERAIRAN CIREBON CANGKOL, JAWA BARAT - Oktafiani, Rizka; M.Pi., Asriyanto; M.Pi., Pramonowibowo (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
Cangkol waters is one of Cirebon’s area which has potensial of demersal fish has about 249,66 ton/year. Lutjanus argentimaculatus fish is one of demersal species the important economic and be the main target of the arrest. The success for fishing by using hand line does not only dependent on the use of the hook, but also bait that used to obtain the expected result. The study was conducted by hand line with the hook and bait treatments are different. The aims of the research are to know the effect of hook constructions (single and sequential double), the effect of bait types (live shrimp and pieces of squid) and the presence or absence of interaction between two factors towards the number of catch Lutjanus argentimaculatus. The method which are used in this research is experimental fishing method. The result of this research showing that the differences of hook construction effect to the catch, which is the sig values number of the catch are (0.000) <0.05 H0 is rejected, while the use of different types of bait did not effect to the catch, which is the sig values number of the catch are (0.109)> 0.05 H0 accepted. There is no interaction between the two factors are different bait and hook. So, the conclusion is that the use of single hook with yellow prawn bait although squid is better than using the sequential double.